UNcleProt (Universal Nuclear Protein database of barley): The first nuclear protein database that distinguishes proteins from different phases of the cell cycle. (2nd January 2017) - Blavet, Nicolas; Uřinovská, Jana; Jeřábková, Hana; Chamrád, Ivo; Vrána, Jan; Lenobel, René; Beinhauer, Jana; Šebela, Marek; Doležel, Jaroslav; Petrovská, Beáta
ABSTRACT: Proteins are the most abundant component of the cell nucleus, where they perform a plethora of functions, including the assembly of long DNA molecules into condensed chromatin, DNA replication and repair, regulation of gene expression, synthesis of RNA molecules and their modification. Proteins are important components of nuclear bodies and are involved in the maintenance of the nuclear architecture, transport across the nuclear envelope and cell division. Given their importance, the current poor knowledge of plant nuclear proteins and their dynamics during the cell's life and division is striking. Several factors hamper the analysis of the plant nuclear proteome, but the most critical seems to be the contamination of nuclei by cytosolic material during their isolation. With the availability of an efficient protocol for the purification of plant nuclei, based on flow cytometric sorting, contamination by cytoplasmic remnants can be minimized. Moreover, flow cytometry allows the separation of nuclei in different stages of the cell cycle (G1, S, and G2). This strategy has led to the identification of large number of nuclear proteins from barley ( Hordeum vulgare ), thus triggering the creation of a dedicated database called UNcleProt, http://barley.gambrinus.ueb.cas.cz/ .